METHODOLOGY FOR DETERMINING AN EFFECTIVE VARIANT OF WAREHOUSE OPERATION TECHNOLOGY WHEN USING HIGHLY MANOEUVRABLE AND ENERGY-EFFICIENT MULTI-AXLE VEHICLES - Pavlenko, O.; Kalinichenko, O. (Municipal economy of cities. Series: «Economy science», 2023)
The article establishes that warehousing operations required in the cargo delivery system can take up a significant amount of time and affect the quality of performed work. An analysis of the situation in the warehouse real estate market has shown that there are prospects for the construction and development of existing warehouses through the introduction of new technologies and solutions to improve technical means of production. Therefore, for the rational operation of the entire complex of warehouse operations and the corresponding increase in productivity with a reduction in the cost of delivery of goods in existing warehouses with intensive flows of goods, it is necessary to introduce an efficient warehouse technology using highly manoeuvrable and energy-efficient multi-axle vehicles. The article analyses the scientific developments of the theoretical foundations for determining an effective variant of warehouse technology by Ukrainian and foreign scientists. The work on improving the technology of warehouses and terminals focuses on the development of effective interaction in all areas of warehouse operations under the influence of random factors. The analysis of the technology of warehouses operating in the Ukrainian market has revealed shortcomings in its organisation: possible options for performing basic warehouse operations when changing the values of technological process parameters are not taken into account, warehouse resources are not used effectively to perform the relevant operations, and opportunities for introducing new technologies into the warehouse technology are not taken advantage of. It is proposed to determine an effective variant of the warehouse operation technology when using highly manoeuvrable and energy-efficient multi-axle vehicles to consider this process in the form of two variants of their organisation with the participation of an electric forklift (first variant) and the proposed mechanism (second variant). To form these variants, the sequence of warehouse operation technology, technical characteristics of mechanisation equipment, and a schematic representation of a warehouse with racks have been determined. The total area of the warehouse was chosen as the objective function of solving the problem of determining an effective variant of warehouse technology when using highly manoeuvrable and energy-efficient multi-axle vehicles, taking into account the system of constraints. The system of constraints includes the relevant factors of influence: the volume of a unit of cargo that passes through the warehouse; time to perform operations when loading (unloading) cargo in the warehouse; time to perform operations when moving cargo by a forklift in the warehouse; loading of a unit of cargo on the warehouse area.